Use Of Pesticides In Nepal And Impacts On Human Health And Environment - Sharma, DR; Thapa, RB; Manandhar, HK; Shrestha, SM; Pradhan, SB (Journal of Agriculture and Environment, 2013)
Majority of the farmers are unaware of pesticide types, level of poisoning, safety precautions and potential hazards on health and environment. According to the latest estimate, the annual import of pesticides in Nepal is about 211t a.i. with 29.19% insecticides, 61.38% fungicides, 7.43% herbicides and 2% others. The gross sale value accounts US $ 3.05 million per year. Average pesticides use in Nepal is 142 g a.i./ha, which is very low as compared to other Asian counties. The focus of this paper is to analyze the use and application status of pesticides in Nepal to aware the society about adverse effects of chemical pesticides in the environment . Pesticidal misuse is being a serious concern mainly in the commercial pocket areas of agricultural production, where farmers are suffering from environmental pollution. Incidence of poisoning is also increasing because of intentional, incidental and occupational exposure. Toxic and environmentally persistent chemicals are being used as pesticides. Many studies showed that the chemical pollution of the environment has long-term effects on human life. It is therefore essential that manufacture, use, storage, transport and disposal of chemical pesticides be strictly regulated. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 67-72 DOI: http://dx.doi.org/10.3126/aej.v13i0.7590